The Influence of Nano-SiO2 and Recycled Polypropylene Plastic Content on Physical, Mechanical, and Shrinkage Properties of Mortar - Haiming Chen; Yangchen Xu; Donglei Zhang; Lingxia Huang; Yuntao Zhu; Le Huang (Advances in Civil Engineering)
This work is aimed to study the possibility of recycling plastic waste (polypropylene (PP)) as aggregate instead of sand in the manufacturing of mortar or concrete. For this, an experimental study was carried out to evaluate the influence of nano-SiO2 and recycled PP plastic particles' content on physical, mechanical, and shrinkage properties and microstructure of the mortars with recycled PP plastic particles. The sand is substituted with the recycled PP plastic particles at dosages (0%, 20%, 40%, and 60% by volume of the sand). The nano-SiO2 content is 5% by weight of cement. The physical (porosity, water absorption, and density), mechanical (compressive and flexural strength) and shrinkage properties of the mortars were evaluated, and a complementary study on microstructure of the interface between cementitious matrix and PP plastic particles was made. The measurements of physical and mechanical properties showed that PP-filled mortar had lower density and better toughness (higher ratio of flexural strength to compressive strength). However, the compressive strength and flexural strength of PP-filled mortar is reduced, and the porosity, water absorption, autogenous shrinkage, and dry shrinkage increased as compared to normal cement mortar. The addition of nano-SiO2 reduced the porosity, water absorption, and drying shrinkage of PP-filled mortar and effectively improved the mechanical properties, but increased its autogenous shrinkage. A microscopic study of the interfacial zone (plastic-binder) has shown that there is poor adhesion between PP plastic particles and cement paste. From this work, it is found that recycled PP plastic waste has a great potential to be a construction material. It can be used as partial replacement of natural aggregates instead.